Does Social Support Contribute To Career Adaptability? Study at The Final Year Student - Yunanda Restu Dewani; Siti Nuzulia (Publikasi Indonesia, 2024)
Final-year students will experience a transition period from lectures to the world of work. The transition period can be challenging for final students. Unpreparedness in facing the transition period can cause various difficulties for final year students, such as unemployment, turnover, and working in inappropriate fields. In addition, students are in the early adult stage of development and are required to start working and develop their careers. This study aims to determine the relationship between social support and career adaptability by controlling for demographic variables, namely gender, educational background, and socioeconomic status in final-year students. This study used a quantitative approach involving 274 respondents. Data analysis using multiple regression analysis showed that social support (family support, friend support, and significant other support) positively affected career adaptability. Educational background also has a positive influence on career adaptability. Gender and socioeconomic status did not influence career adaptability.